1987
DOI: 10.1099/0022-1317-68-10-2639
|View full text |Cite
|
Sign up to set email alerts
|

cDNA Cloning and Sequence Analysis of the Gene Encoding the Peplomer Protein of Feline Infectious Peritonitis Virus

Abstract: SUMMARYThe peplomer gene of feline infectious peritonitis virus (FIPV) strain 79-1146 was isolated from a genomic cDNA library by differential hybridization with RNA 2 and 3 as probes. From the nucleotide sequence a primary translation product of 1452 residues (Mr 160472) was predicted, containing an N-terminal signal sequence, a C-terminal transmembrane segment and 35 potential N-linked glycosylation.sites. By S1 nuclease analysis the 5' end of the presumptive RNA 2 body was located at about 30 nucleotides up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 38 publications
0
47
0
Order By: Relevance
“…None of the recombinants isolated from our cDNA library contained the poly(A) tail, probably because the cDNA synthesis was randomly primed by calf thymus DNA pentamers (de Groot et aL, 1987b). If aligned to the TGEV sequence, the most 3' located clone, E7, ends just one nucleotide upstream of the poly(A) tail.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the recombinants isolated from our cDNA library contained the poly(A) tail, probably because the cDNA synthesis was randomly primed by calf thymus DNA pentamers (de Groot et aL, 1987b). If aligned to the TGEV sequence, the most 3' located clone, E7, ends just one nucleotide upstream of the poly(A) tail.…”
Section: Resultsmentioning
confidence: 99%
“…Selection and analysis of cDNA clones cDNA clones containing sequences derived from the 3' end of the FIPV genome were selected from a "random" cDNA library of FIPV 79-1146 genomic RNA (de Groot et al, 1987b) by hybridization to sucrose-gradient purified, 32p-labeled FIPV RNA 6 in 50% formamide, 5× SSC, 5X Denhardt's , 100 #g/ml salmon sperm DNA at 42 °. Recombinant DNA techniques were performed by standard methods (Maniatis et al, 1982).…”
Section: Methodsmentioning
confidence: 99%
“…possibility that such an RNA may be synthesized at a low level must be considered because a CTAAAC signal was observed. Similarly, in the case of FIPV strain 79-1146 no RNA has been detected between RNA 3 and the membrane polypeptide RNA (de Groot et al, 1987) but the possibility of an equivalent of the TGEV RNA 4 has been alluded to (de Groot, 1989). Thus, the numbering conventions employed do not deal adequately with the variations in expression strategy observed in this region of genome within this group of closely related viruses.…”
Section: Ggtctttcaaccctgaaactagcgcaattctttgcgttagtgcgttaggaagaagctatgmentioning
confidence: 99%
“…TGEV, PRCV and FIPV have been characterized in some detail and the genes encoding the structural proteins have been cloned and sequenced (de Groot et al, 1987;Vennema et al, 1991 ;Britton etal., 1988a, b;Rasschaert &Laude, 1987;Rasschaert et al, 1990). A comparison of the available FIPV amino acid sequences with the corresponding sequences of TGEV and PRCV has revealed that the structural genes are very closely related.…”
Section: Introductionmentioning
confidence: 99%
“…To date, no antigenic determinants for any coronavirus E2 protein have been mapped to specific E2 gene sequences, although this gene from several coronaviruses has been sequenced and MAbs have been produced (Binns et al, 1985;Schmidt et al, 1987;Luytjes et al, 1987;Rasschaert & Laude, 1987;de Groot et al, 1987). However, Makino et al (1987) have localized neutralizing determinants to the carboxy-terminal one-third of the E2 protein for mouse hepatitis virus (MHV) by analysis of RNA recombinants with crosses within the gene encoding The aim of this study was to identify these determinants and begin to relate that information to the structure of the BCV E2 protein.…”
Section: Introductionmentioning
confidence: 99%